Malformations, genetic abnormalities, and wilms tumor. Issue 1 (23rd August 2013) - Dumoucel, S.; Gauthier‐Villars, M.; Stoppa‐Lyonnet, D.; Parisot, P.; Brisse, H.; Philippe‐Chomette, P.; Sarnacki, S.; Boccon‐Gibod, L.; Rossignol, S.; Baumann, C.; Aerts, I.; Bourdeaut, F.; et al.
Abstract Background Wilms Tumor (WT) can occur in association with tumor predisposition syndromes and/or with clinical malformations. These associations have not been fully characterized at a clinical and molecular genetic level. This study aims to describe clinical malformations, genetic abnormalities, and tumor predisposition syndromes in patients with WT and to propose guidelines regarding indications for clinical and molecular genetic explorations. Procedure This retrospective study analyzed clinical abnormalities and predisposition syndromes among 295 patients treated for WT between 1986 and 2009 in a single pediatric oncological center. Results Clinically identified malformations and predisposition syndromes were observed in 52/295 patients (17.6%). Genetically proven tumor predisposition syndromes (n = 14) frequently observed were syndromes associated with alterations of the chromosome WT1 region such as WAGR (n = 6) and Denys–Drash syndromes (n = 3), syndromes associated with alterations of the WT2 region (Beckwith–Wiedeman syndrome, n = 3), and Fanconi anemia (n = 2). Hemihypertrophy and genito‐urinary malformations (n = 12 and n = 16, respectively) were the most frequently identified malformations. Other different syndromes or malformations (n = 10) were less frequent. Median age of WT diagnosis was significantly earlier for children with malformations than those without (27 months vs. 37 months, P = 0.0009). There was no significant difference in terms of 5‐year EFS and OS between WT patients without or with malformations. Conclusions The frequency of malformations observed in patients with WT underline the need of genetic counseling and molecular genetic explorations for a better follow‐up of these patients, with a frequently good outcome. A decisional tree, based on clinical observations of patients with WT, is proposed to guide clinicians for further molecular genetic explorations. Pediatr Blood Cancer 2014;61:140–144. © 2013 Wiley Periodicals, Inc.